Increased brain activation and functional connectivity after working memory training in patients with ischemic stroke: an fMRI study - Chen, Zhengwei; Yun, Xiaoping (Frontiers in Stroke, 2023)
Objective Working memory (WM) impairment is common in patients after a stroke. WM training (WMT) has been suggested as a way to improve cognitive function. However, the neural effects following WMT in stroke patients remain largely unclear. This study aimed to explore the behavioral changes and neural effects of WMT on patients with chronic ischemic stroke. Methods Fifty first-ever ischemic stroke patients with WM deficits in the chronic stage were randomly assigned to either a 4-week WMT group or a control group. Verbal n-back, digital and spatial memory-span, Raven's standard progressive matrices, and the Stroop color-word test, as well as task-state and resting-state fMRI were assessed for all patients at baseline and after the intervention. Results The WMT group showed improvements in WM, fluid intelligence, and attention after training. Additionally, the WMT group exhibited increased activation in the left middle frontal gyrus (MFG) and middle occipital gyrus after training. At baseline, all patients were impaired in their abilities to elevate activation in their WM network as a response to increasing WM load. However, in the WMT group, increased activation was observed in the left cerebellum anterior lobe, right cerebellum posterior lobe (CPL), and MFG in the 2-back vs. 1-back contrast after WMT. We also found increased functional connectivity between the left MFG and the left inferior parietal lobule (IPL), and between the bilateral IPL and the right CPL after training in the WMT group. Conclusion Our study supported that WMT potentially improved WM capacity in ischemic stroke patients during the chronic stage, and that the training effects might transfer to fluid intelligence and attention ability. Our results also demonstrated that repeated WMT potentially increased brain activation and resting-state functional connectivity within the WM network in patients with ischemic stroke. These findings provided robust evidence to support WMT as an effective intervention to enhance cognitive rehabilitation and shed light on the functional neuroplasticity mechanism of WMT on cognitive recovery after ischemic stroke.